Re-surveying breeding forest bird communities in Western Oregon after 50 years: comparing 1968–1970 and 2020–2021 - Nolan Clements; W. Douglas Robinson (Biodiversity Data Journal)
Accurate assessments of changes in breeding bird populations require regular, structured surveys or, alternatively, carefully documented benchmarks that can be precisely repeated. We re-surveyed a historic benchmark of forest bird communities in Western Oregon, USA, originally conducted by Stanley Anderson between 1968-1970. Anderson’s thesis uniquely preserves detailed plot locations, species density estimates, vegetation structure summaries and methodological descriptions — an uncommon level of documentation for the time. To facilitate accurate comparisons and future re-surveys, we explain how we aligned our methods with Anderson’s and incorporated modern bird counting techniques. We also provide our raw data, metadata and methodological details to ensure transparency and reproducibility.Anderson’s work presents unusually old and detailed datasets of forest bird communities preserved from the Pacific Northwest, USA. It provides a unique opportunity to examine long-term changes in breeding bird communities within these forested landscapes affected by anthropogenic influence. The data and methods presented here are well-documented, ensuring that this benchmark can be effectively used for precisely repeatable re-surveys and comparative studies.